The Influence of Diabetes Mellitus on Survival of Abdominal Perforator Flaps: An Experimental Study in Rats with Slowly Induced Diabetes Mellitus - Baldea, Bogdan Ionut; Toader, Septimiu; PhD, Pavel Orbai; Barsan, Simona; Olariu, Radu; Grigorescu, Dan Ovidiu; Penciu, Marius; Nagy, Andras Laszlo; Georgescu, Alexandru Valentin (Journal of Reconstructive Microsurgery, 2015)
Background Lower limb ulcers are a major source of morbidity and mortality in diabetic patients. Surgical coverage of these wounds is fraught with a high complication rate. Although clinically perforator flaps lead to good results in diabetic patients, there is little experimental data to support this finding.Methods A total of 60 Wistar rats were randomly assigned either to the diabetic (n = 30) or control (n = 30) group. Diabetes was induced by streptozotocin injection at 50 mg/kg body weight and was confirmed by blood glucose levels > 180 mg/dL preoperatively. In all rats, a cranial epigastric artery perforator flap was raised. At postoperative day 7, all flaps were raised, photographed by digital planimetry, and analyzed histologically.Results Mean glycemic levels preoperatively were 207.8 ± 16 in the diabetic group and 82.8 ± 5.1 in the control group (p < 0.05). Ninety percent of the flaps survived completely in the control group, compared with 66.7% in the diabetic group (p < 0.05). The mean flap survival area was lower in the diabetic group (83.3 ± 16.5%) than in the control group (96 ± 4%). There were significantly more perioperative complications in the diabetic group (46.7%) than in the control group (16.7%), but these did not affect flap survival. Superficial ulceration appeared only in the diabetic group as a complication.Conclusion Perforator flaps can be successfully used for coverage of cutaneous defects in a rat diabetic model. These flaps show higher complication rates in diabetic versus nondiabetic animals; however, this complication rate has little influence on flap survival.
Keywords: streptozotocin; rat; diabetes mellitus; perforator; flap